2012
DOI: 10.1007/s12020-012-9811-z
|View full text |Cite
|
Sign up to set email alerts
|

Thin core biopsy should help to discriminate thyroid nodules cytologically classified as indeterminate. A new sampling technique

Abstract: Indeterminate neoplasms (IN) represent the gray zone of thyroid cytology in which malignant and benign tumors cannot be discriminated. Recently, the approach by thin core needle biopsy has been proposed. Here we report a new thin core needle biopsy approach in 40 consecutive patients with thyroid IN at cytology. In this study, a 21-G needle was inserted into the nodule, advanced within the lesion, and moved ahead reaching extranodular tissue. The resulting sample allowed to evaluate the cytomorphology of nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 26 publications
5
96
0
1
Order By: Relevance
“…18 These problematic nodules should be diagnosed on US before any intervention. Circumscribed solid nodules without malignant features are considered an indeterminate category on US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 These problematic nodules should be diagnosed on US before any intervention. Circumscribed solid nodules without malignant features are considered an indeterminate category on US.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggested that the use of a CNB technique that biopsied the capsule of the thyroid nodule and the surrounding parenchyma was useful for the diagnosis of cytologically indeterminate nodules. 18 However, the authors did not compare the results of the conventional method with those of the modified method or focus on the diagnosis of problematic nodules by using a conventional CNB method. We evaluated whether the modified CNB technique was more effective in the diagnostic yield of circumscribed solid nodules without malignant sonographic features with indeterminate cytology compared with a conventional method.…”
mentioning
confidence: 99%
“…The latter cytological picture occurs quite frequently (10-26 % of nodules) and harbors an intermediate risk of malignancy (14-48 %). Improvements of thyroid cytopathology by the introduction of thin core needle biopsy, with the assessment of the nodule capsule and the perinodular tissue, have appeared to ameliorate recognition of malignancy in cytologically indeterminate nodules [9]. Similarly, combination of nodule ultrasound features with measures of nodule stiffness, obtained by real-time elastography, has appeared to increase sensitivity for malignancy and to strengthen the selection of patients who do not need further diagnostic testing [10].…”
mentioning
confidence: 99%
“…Firstly, it helped us to rule out a possible metastatic thyroid disease which would have driven to completely different diagnostic and therapeutic choices, with no preliminary open surgical biopsy of the lymph node needed, provided it had been adequately evaluated by CNB. Besides, CNB of the neck lesion was performed by a 21-gauge needle, which in other papers concerning thyroid biopsy proved to have a good tolerability by patients [15], with low complication rates [5]. Focusing on soft tissue tumors, in our opinion more studies would be necessary in order to establish the proper role of CNB within the diagnostic work-up [16].…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we decided to perform a core needle biopsy (CNB) of the neck mass. After administration of local anesthesia by mepivacain 1 % mL, a 21-gauge modified Menghini cutting needle (Biomol Ò , Hospital Service, Rome, Italy) was percutaneously introduced under ultrasound guide in freehand fashion, as recently described for thyroid lesions [5] (Fig. 1b).…”
Section: Case Reportmentioning
confidence: 99%